Reading skill builders series for Filipino high school students (with Grade Level 4.5-4.9) Diamond set - Medina, Rose (Osorio) 1925- (s.n.], 1969)
To improve the reading skills of Filipino high school students, this seminar paper offers materials for individualized instruction in reading. With this Reading Skill Builders Series, an auxiliary to the ongoing reading program in school is provided to further individualized work or to put more stress on the program's instructional content. An optional approach to teaching reading that will allow the formation of sets appropriate to different kinds of reading material within the student is also given and the mature reader's effective purpose of finding reading purposes within himself is emphasized.